ANALISIS PELAKSANAAN PROGRAM COMMUNITY DEVELOPMENT PT SUMATERA SYLVA LESTARI (SSL) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI ROKAN HULU - Dedi Saputra; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Corporate Social Responsibility is one of the obligations that must be implemented by the company in accordance with the contents of article 74 of law number 40 year 2007 about limited liability company (UUPT). The Company is led to exercise and grant the rights of communities and the environment mandated by law to the company. CSR is a logical consequence of the existence of a state-given right to the enterprise to live and thrive in an area of the environment. As a large company, PT Sumatera Sylva Lestari explores nature in an environment, either directly or indirectly in contact with the local ecosystem. That matter declare that PT Sumatera Sylva Lestari shall be responsible for all consequences caused either intentionally or unintentionally to the stakeholders. The purpose of this research is to know and analyze the implementation of community development program as a form of social responsibility of PT Sumatera Sylva Lestari in Improving People's Welfare in Rokan Hulu.The method used in this research is descriptive qualitative method. Research subjects were determined based on purposive technique.. Data collection techniques include observation, interviews and documentation. Data analysis techniques using Miles and Huberman interactive and model. While the examination techniques of data validity include triangulation and reference adequacy.The results of research on the implementation of the community development program as a form of social responsibility PT Sumatera Sylva Lestari in Improving the Welfare of the Society concluded walking pretty well. PT Sumatera Sylva Lestari has done its social responsibility through partnership program between company and society especially local people. The partnership is realized in the Desa Maju Peduli Api (DMPA) program to help improve the long-term welfare of the local community by providing production facilities to the community for 2 years the capital will be returned to the company to be given to other communities.Keyword: Analysis, Community development, Descriptive qualitative methode